2001
DOI: 10.1046/j.1365-2044.2001.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Xenon expenditure and nitrogen accumulation in closed‐circuit anaesthesia

Abstract: SummaryThe high price of xenon has prevented its use in routine, clinic anaesthetic practice. Xenon therefore has to be delivered by closed-circuit anaesthesia. The accumulation of nitrogen is a significant problem within the closed circuit and necessitates flushing, which in turn increases gas expenditure and costs. In previous investigations, nitrogen concentrations between 12% and 16% have been reported in closed-circuit anaesthesia. In order to avoid such nitrogen accumulation, we denitrogenised seven pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…21 These techniques will reduce strange gas accumulation over time and thus limit the necessity to flush the system. Recycling of xenon is not an option for a reduction in overall consumption, because only 1-2 l will be exhaled during the short recovery from anaesthesia (3.6 min to extubation) 22 due to the long half-life of 97 min.…”
Section: Discussionmentioning
confidence: 99%
“…21 These techniques will reduce strange gas accumulation over time and thus limit the necessity to flush the system. Recycling of xenon is not an option for a reduction in overall consumption, because only 1-2 l will be exhaled during the short recovery from anaesthesia (3.6 min to extubation) 22 due to the long half-life of 97 min.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies repeatedly demonstrated that consumption and/or waste of xenon was remarkably elevated within the wash-in period aiming to remove accumulated nitrogen and accelerate time to target concentration of xenon [15], [22]. It`s important to note that a significant and irreducible part of xenon used during wash-in corresponds to the xenon volume needed to saturate the fast compartment of the patient`s body (several litres of xenon) as well as to saturate the respirator internal volume and tubes (estimated to 3l xenon).…”
Section: Discussionmentioning
confidence: 99%
“…However, time of pre-oxygenation (before intubation) and denitrogenation (after intubation) was comparable between the groups. While use of high-flow is frequently necessary during wash-in period, previous studies already supposed induction period to offer most potential to reduce waste of xenon [15], [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Maßnahmen zur Reduktion des Xenonverbrauchs wurden daher angestrebt. Durch die Verwendung von geschlossenen Narkosesystemen liegt der Xenonverbrauch verglichen mit Low-Flow-Systemen bei einem Zehntel [57]. Zur Reduktion des Xenonbedarfs wurden in der Vergangenheit Ansätze zur i. v. Applikation einer Xenon-Lipidemulsion beschrieben [58].…”
Section: Xenonunclassified